The effect of one year lifestyle intervention on eGFR in children and adolescents with overweight, obesity and morbid obesity - van Dam, Mark (Sci Rep, 2019)
Obesity causes modifications in the kidneys reversed by weight loss in adults. There is little data on renal function and effects of weight loss in children with obesity. The aim of this prospective study was to examine renal function and effect of a lifestyle intervention in children with overweight, obesity and morbid obesity. Two hundred forty-five children (age 12.4 ± 3.3 years, 40% boys, BMI z-score 3.46 ± 0.70) participating in an out-patient lifestyle intervention were included. Children with at least 12 months follow-up (n = 144 (58.8%)) were included in the longitudinal study. Anthropometry, blood analysis and blood pressure measurements were performed at baseline and follow-up. Glomerular filtration rate (GFR) was estimated using the Schwartz and FAS equation. eGFR was de-indexed using body surface area. Different cut-off points for defining glomerular hyperfiltration were used for stratification. Depending on the definition and equation used, glomerular hyperfiltration was present in 2% to 18% of the participants. After intervention, de-indexed eGFR decreased significantly in children with baseline glomerular hyperfiltration, depending on the eGFR equation and definition for glomerular hyperfiltration used. No associations of changes in eGFR with changes in BMI z-score, blood pressure or parameters of glucose and lipid metabolism were found. In conclusion, after one year of lifestyle intervention, eGFR decreases in hyperfiltrating children and adolescents with overweight, obesity and morbid obesity. eGFR and changes over time in children with obesity depend on eGFR equation used and on de-indexing for body surface area.